Correction of a Severely Rotated Mandibular Canine in an Adult Patient Using Invisalign: A Case Report - Pando, Karina Andrea; Aguilar, Edison Román; Bravo, Manuel Estuardo (Open Science Journal, 2018)
Introduction: The Invisalign system has been used in the orthodontic treatment of numerous types of malocclusions. However some clinicians have reported difficulty incorrecting rotations particularly in canines and premolars using the Invisalign appliance system. This case report describes the orthodontic treatment of an adult patient with severe canine rotation (more than 45°) and crowding on upper and lower tooth. Methods: The clinical examination included extra-oral and intra-oral photographs, panoramic radiographic, lateral cephalometric, stone casts, and upper and lower arch analysis obtained from ClinCheck 3.0.The treatment planning was resolved the crowding in both upper and lower arches and the severe rotation of 33 tooth (46°) using Invisalign system as well as the canine and molar relationship, dental verticalization, adequate over jet, overbite and dental midline using the same system. The duration of the treatment was approximately eight months. Results: In Post-treatment extra oralphotographs, no significant changes were observed at the end of the treatment. Intraoral photographs showed an important and notable improved aesthetics. The canine relationship improved slightly and molar Class Irelationship was maintained. An increase in transverse diameter was observed at the level of first premolars, second premolars and first molars. The overbite was improved. The crowding and the severe canine rotation were corrected. No obvious root resorption was radiographically evident and slight cephalometric changes. Conclusion: The treatment with the Invisalign system resolved the complaint of our patient so this system could be considered as an option that offered good results in the treatment of upper and lower crowding of arches involving severe canine rotation.